Fertility differentials and educational attainment in Portugal: a non-linear relationship - Oliveira, I. (Canadian Studies in Population, 2009)
This analysis of the Portuguese case shows a non-linear relationship between the number of children and education in recent years. Using the data from ten years before this hypothesis was confirmed, and we can see that the general decline in Portuguese fertility within the last decade was due to the fertility decrease of the less educated people, although partly attenuated by the fertility increase of the upper social groups. The reasons for a non-linear relationship are discussed within the context of female employment rates and salary differentials by educational attainment. The main hypothesis is that differences in fertility are related to an 'education-work' effect amongst those in the less educated groups and to an 'education-income' effect amongst the more educated.